Insar measurements at high latitudes. - Andra Baduge, Anura Terance Wickramanayake (Cranfield University, 2014)
This thesis contributes towards understanding of Interferometric Synthetic Aperture Radar (InSAR) measurements at high latitudes. Luossavaara-Kiirunavaara Aktiebolag (LKAB) mining company, the sponsor of this Ph.D. research, intends to use the InSAR techniques for subsidence measurements around the Kiruna underground iron ore mine. The Kiruna underground iron ore mine is located in direct proximity to the city of Kiruna, with the active mining area currently about 1 km west of the city center (67°51'20" N, 20°13'30 E). At present LKAB is exploring the possibility of using InSAR measurements as an operational technique for subsidence measurements. High latitudes InSAR measurements are known to be particularly affected by long periods of ground snow cover that contributes to temporal de-correlation between subsequent radar images. The objectives of this Ph.D. research are (1) to quantify the seasonal effects in InSAR measurements and (2) to identify techniques to improve the high latitude InSAR measurements. In this research study, spatial coherence was used to quantify the seasonal effects in the Differential InSAR (DInSAR) measurements for Kiruna region. A comparison between Static Global Positioning System (Static-GPS) and Corner Reflector InSAR (CRInSAR) measurements were carried out to quantify the seasonal effects in CRInSAR measurements. Spatial ground deformation patterns were used to improve the DInSAR measurements. A theoretical analysis for compact active transponders (CAT) was carried out to improve the North-South InSAR measurements. DInSAR, CRInSAR and Coherent Target Monitoring (CTM) techniques were used to evaluate the applicability of InSAR techniques for high latitude mining induce deformation measurements. The results show seasonal variations in DInSAR, CTM and CRInSAR measurements. Furthermore, DInSAR measurements around the Kiruna iron ore mine can be improved up to sub-centimeter accuracies by using the spatial ground deformation patterns. Also, the compact active transponders identi ed as a possible candidate to improve the accuracy of the North-South InSAR measurements. It is concluded that, all InSAR techniques (DInSAR, CTM and CRInSAR) were affected by the winter snow condition, and only the summer (snow-free) months are suitable for ground deformation measurements. Moreover, the study shows that without the winter images still it is possible to achieve accurate CTM and CRInSAR time series estimations for Kiruna. The East-West vector is the least noisy deformation vector, and both East-West and vertical vectors can be used to determine the LKAB environmental criterion. At present, every year, LKAB is acquiring 45 Radarsat-2 images from three beam modes. However, this study shows that less than 35% of those data are useful for subsidence measurements.